A quantitative assessment method for the space design of products based on ergonomics and virtual simulation. - Ziyue Guo; Dong Zhou; Pengyan Liu; Zhiyi He; Chuan Lv (PLoS ONE, 2018)
Work spaces for assembly or maintenance operations are considered in the design stage of products. Maintenance space is a key factor in determining how well a product can be maintained. If the work space is sufficiently considered in the design stage, it will benefit both the user and the maintainer. From a maintenance perspective, this paper proposes a quantitative method to evaluate the maintenance space by virtual simulation and consideration of ergonomics. In this method, maintenance operations are concisely classified into three types. Based on the virtual simulation of the maintenance process and maintainer data, the swept volume of a hand is built using envelope theory. The operation range of the maintainer is derived by establishing a mathematical model for the upper limb. Combining the swept volume and operation range, the maintenance space can be quantitatively evaluated. A concise validation demonstrates that the proposed method is effective for evaluating the maintenance space to improve the space design. The proposed method could be applied to the space design of a complex product.